Intertextuality in 1 Cor 15:54-55. A Call for Comfort and Admonition - Steffen Jöris (Protokolle zur Bibel, 2015)
In 1 Corinthians 15, Paul reaffirms the belief in the resurrection of Jesus, which also functions as a justification for the Christian faith. Towards the end, he describes the victory over death through Jesus, which includes the saying “Death is swallowed up in victory. O death, where is your victory? O death, where is your sting?” in 1 Cor 15:54-55. It is well known that this saying alludes to Isa 25:8 and Hos 13:14. The function of this intertextual reference remains dubious however, especially since there seems to be no explicit reason why Paul might want to combine these two OT passages. This paper argues for a deliberate intertextual allusion that takes the context of Isa 25:8 and Hos 13:14 into account and reads the saying within 1 Cor 15:54-58, which shows that Paul’s theological interpretation of the resurrection has a twofold nature that is both comforting and admonishing. He takes Jesus to be the fulfilment of the promise made in Isa 25:8 and uses the context of Hosea 13 to present a warning to the Corinthian church to remain steadfast in Christ.